Climate change scenarios predict reduction in suitable habitats and range shifts for Ophiocordyceps sinensis (Berk.) in Hindu Kush Himalaya - Salam, Nadeem; Sidhu, Harvinder Kaur; Shaban, Shaheeda; Reshi, Zafar A.; Shah, Manzoor A. (Journal of Asia-Pacific biodiversity, 2025)
The Hindu Kush Himalayan region has seen a faster pace of anthropogenic climate warming than the global average during the last 50 years. Since the 1980s this region has been experiencing intense climatic events, notably elevation-dependent warming. Given its unique evolutionary background, rich variety of species, and significant endemism, it is crucial to comprehend the effects of climate change on species distributions in this area. Of particular interest are the fungi, which have been the subject of much fewer studies on how they will respond to climate change, despite the fact that they may have a significant role in the functioning and stability of ecosystems. We therefore selected Ophiocordyceps sinensis an alpine fungus species for predicting the effects of climate change on its distribution in Hindu Kush Himalaya. Regarded as one of the most expensive natural resources used in oriental medicine, Ophiocordyceps and its surrounding habitats are under threat from various ecological and anthropogenic factors. We used species distribution modeling software Maxent 3.3.4 and a set of uncorrelated climatic (temperature and precipitation) and topographical (elevation, slope, and aspect) variables at a spatial resolution of 2.5 arc minutes to model the suitable habitats. To predict the future distribution of O. sinensis we used future climate data from BCCCSM2- HR global circulation model for three emission scenarios of the shared socioeconomic pathways (SSPs) (SSP126, SSP245 and SSP585). Maxent model predicted current and future habitats with high accuracy. Current potential distribution map of O. sinensis shows that high suitability areas occur in India, China, Nepal, and Bhutan. Prediction maps under all three scenarios showed a large reduction in suitable habitats as compared to current climatic conditions. Analysis of range change reveals that species exhibit both range expansion and range contraction under climate change scenarios. Range contraction is noticeably more than range expansion, causing an overall reduction in the suitable habitats occupied by O. sinensis. “Centroid Range Shift” analysis revealed potential suitable habitats will shift to the southwest direction under all future scenarios with almost overlapping centroids.